Riverine Ecosystem Management 2018
DOI: 10.1007/978-3-319-73250-3_3
|View full text |Cite
|
Sign up to set email alerts
|

River Morphology, Channelization, and Habitat Restoration

Abstract: Authorities and planners involved in river restoration projects often tend to focus on the hydromorphological state of a short river reach or certain aquatic habitats where the pending deficits are most evident. Nevertheless, for long-term and sustainable restoration, one should also consider flood dynamics and other interlinked processes at larger spatiotemporal scales, ideally at the catchment scale. Moreover, restoring river morphology also calls for the consideration of the dynamic processes of the whole f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 74 publications
(60 reference statements)
0
30
0
Order By: Relevance
“…Interestingly, while Batalla, Gómez, and Kondolf () and Radinger, Alcaraz‐Hernández, et al () revealed that hydrologic alteration in the Ebro basin is most pronounced in downstream proximity to dams, our results revealed highest numbers of alien species in 25–60 km distance downstream of dams. The ultimate reason for this downstream shifted effect remains unclear, but might be related to the so‐called “rhithralization” effect (Hohensinner, Hauer, & Muhar, ). By that, reaches immediately downstream of dams may show relatively elevated flow velocities and larger grain sizes of the substrate, which might benefit the native rheophylic, lithophylic species (e.g., Ebro barbel) rather than the limnophilic alien species (e.g., largemouth black bass [ Micropterus salmoides ]).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while Batalla, Gómez, and Kondolf () and Radinger, Alcaraz‐Hernández, et al () revealed that hydrologic alteration in the Ebro basin is most pronounced in downstream proximity to dams, our results revealed highest numbers of alien species in 25–60 km distance downstream of dams. The ultimate reason for this downstream shifted effect remains unclear, but might be related to the so‐called “rhithralization” effect (Hohensinner, Hauer, & Muhar, ). By that, reaches immediately downstream of dams may show relatively elevated flow velocities and larger grain sizes of the substrate, which might benefit the native rheophylic, lithophylic species (e.g., Ebro barbel) rather than the limnophilic alien species (e.g., largemouth black bass [ Micropterus salmoides ]).…”
Section: Discussionmentioning
confidence: 99%
“…River gravel bars are dynamic and heterogeneous habitats ranging from glacial floodplains and alpine wide river valleys to piedmont (Montgomery and Buffington 1998; Malard et al 2006; Tockner et al 2006; Hohensinner et al 2018). Periodical floods together with variation of speed and intensity of the water current, model richly braided channels with a mosaic of channels, pools, bars and islands (Junk et al 1989; Tockner et al 2000; Ward et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Further research [15] compared the differences in geomorphology between natural and regulated streams and their impact on biota, since natural channels differ from prismatic ones by their rich variability of the cross-section (XS) and longitudinal channel profiles. Typical consequences of geometrical river regulations for the biota are the reduction of original instream habitat complexities and habitat availabilities in increasingly uniform riverbeds [21]. It is the morphology of such regulated rivers that is the main reason for the loss of biota and the degradation of the value of the river.…”
Section: Introductionmentioning
confidence: 99%